Taste of a new product: sheep and goat sausages - Rodrigues, Sandra (2014)
This study is part of a Project that aims to study a strategy which gives value-added to sheep and goat meat of animals which have very low price and out of quality label products as “Cabrito Serrano” and “Borrego Transmontano”. Bragançana ewes and Serrana goats’ carcasses were used in the production of a fresh sausage. Transformation was made in a traditional industry, according to 2 main recipes, including or not bonnet pepper. Thus, 4 treatments were considered: ewes with pepper, ewes without pepper, goats with pepper and goats without pepper. Physical, chemical and microbiological analyses were conducted and results published. But it is important to know about this new product sensory characteristics and its acceptability by consumers. So, the objective of this work was to evaluate the sausages sensory characteristics and relate it with consumers’ preferences. Effects of species and pepper were studied and analyzed for odor intensity, strange odor presence, flavor intensity, strange flavor presence, hardness, juiciness, fibers presence, spiciness, sweetness and overall acceptability by a 9 elements semi-trained taste panel, in 4 sessions. And taste, texture and overall acceptability preferences were evaluated by an 82 elements consumers’ panel. A generalized Procrustes analysis and preference mapping were performed to test taste panel and consumers panel evaluations, respectively. Both species and pepper effects were detected by experts. Goat’s sausages were considered by panelists as harder, with more fibers, and less succulent than ewes’ sausages. Pepper sausages presented higher odor intensity, less flavor intensity, less strange odor and flavor presence, and were sweeter and less spicy than sausages without pepper. Consumers showed no preference considering different types of sausage, since none of preferences maps presented significant models for the established classes. This can be important for the sausages commercialization, as all kind of sausages studied in this work can be salable.